2015
DOI: 10.1021/acsami.5b03977
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Evolution of Gyroid-Forming Block Copolymer Thin Films with Varying Solvent Evaporation Rate

Abstract: In this study, we aim to examine the morphological evolution of block copolymer (BCP) nanostructured thin films through solvent evaporation at different rates for solvent swollen polystyrene-block-poly(l-lactide) (PS-PLLA). Interesting phase transitions from disorder to perpendicular cylinder and then gyroid can be found while using a partially selective solvent for PS to swell PS-PLLA thin film followed by solvent evaporation. During the transitions, gyroid-forming BCP thin film with characteristic crystallog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 51 publications
3
36
1
Order By: Relevance
“…[ 42 ] In addition, since the helical phase is an intermediate state in chiral PLA‐containing BCs, it would evolve into equilibrium double‐gyroid phases after annealing for an extended period. [ 40,43 ] The hydrolysis of the PLA block resulted in the formation of a nanoporous PS matrix with gyroid nanochannels, which could function as removable templates to fabricate nanoporous gyroid structures composed of all types of elements and materials for different functions. These functions include, nanoporous gyroid Pt for electrochemical catalysis, nanoporous gyroid metallic oxides for optoelectronic applications, nanoporous epoxy for protein adsorption, and nanoporous Ni/NiO/C composites for electrical properties.…”
Section: Hierarchical Chirality Transfer In Condensed Statesmentioning
confidence: 99%
“…[ 42 ] In addition, since the helical phase is an intermediate state in chiral PLA‐containing BCs, it would evolve into equilibrium double‐gyroid phases after annealing for an extended period. [ 40,43 ] The hydrolysis of the PLA block resulted in the formation of a nanoporous PS matrix with gyroid nanochannels, which could function as removable templates to fabricate nanoporous gyroid structures composed of all types of elements and materials for different functions. These functions include, nanoporous gyroid Pt for electrochemical catalysis, nanoporous gyroid metallic oxides for optoelectronic applications, nanoporous epoxy for protein adsorption, and nanoporous Ni/NiO/C composites for electrical properties.…”
Section: Hierarchical Chirality Transfer In Condensed Statesmentioning
confidence: 99%
“…She et al demonstrated the controlled ordering of the double gyroid morphology in diblock copolymer thin films upon annealing in a neutral solvent and employing a functionalized substrate . Similarly, Wu et al explored the effect of swollen thickness and solvent removal rate on the resulting morphology of solvent‐annealed gyroid‐forming diblock copolymers . Both publications report, however, morphological transitions to the cylinder phase, despite the use of a supposedly neutral solvent.…”
Section: Introductionmentioning
confidence: 99%
“…However, SVA is a more complex process than thermal annealing. The morphology in this process not only depends on the intrinsic properties of BCP, such as the extent of χ , the degree of polymerization ( N ), and the composition (block ratio f ), but also on type of the solvent [12,13,14,15,16,17,18,19] and the film thickness [20,21,22]. Generally, preferentially wetting of one block at the substrate surface or free surface on the contrary induces preferential parallel orientation of domains [22].…”
Section: Introductionmentioning
confidence: 99%